Pecularities of electrical activity of the heart in patients in the acute period of Q-myocardial infarction after primary coronary intervention - Savchenko, Yu.; Kyselov, S.; Кисельов, Сергій Михайлович (My University, 2021)
Aim of the study: To identify features of HRV in patients with acute period of Q-MI after PCI.
Keywords: тези доповідей